2015
DOI: 10.1111/ter.12173
|View full text |Cite
|
Sign up to set email alerts
|

Lateral extrusion along the Altyn Tagh Fault, Qilian Shan (NE Tibet): insight from a 3D crustal budget

Abstract: The lithospheric strike-slip Altyn Tagh Fault has accommodated hundreds of kilometres of displacement between the Qaidam and Tarim blocks since its Eocene reactivation. However, the way the deformation is accommodated in the Qilian Shan and further east remains uncertain. Based on 360 km of north-eastward migration of the relatively rigid Qaidam block along the Altyn Tagh Fault and 3D isovolumetric balancing of the crustal deformation within the Altyn Tagh Fault-Qilian Shan system, we demonstrate that 250 AE 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 77 publications
3
55
0
Order By: Relevance
“…To balance the erosion from the surrounding mountain belts with the deposits preserved in the basin, we assume that Qaidam basin has been internally drained basin since initial subsidence of the basin in the Cenozoic. This inference is supported by recent source‐to‐sink studies that reveal that exhumation of the Altyn Tagh Shan, Eastern Kunlun Shan and the Qilian Shan source regions has provided clastic material to the Qaidam basin since the deposition of Lulehe Formation (Bush et al, ; F. Cheng, Fu, et al, ; F. Cheng, Guo, et al, ; F. Cheng, Jolivet, et al, ; F. Cheng, Jolivet, et al, ; L. Li et al, ; L. Li et al, ; W. Wang, Zheng, et al, ; W. Zhu, Wu, Wang, Fang, et al, ; W. Zhu, Wu, Wang, Zhou, et al, ).…”
Section: Methodsmentioning
confidence: 80%
See 2 more Smart Citations
“…To balance the erosion from the surrounding mountain belts with the deposits preserved in the basin, we assume that Qaidam basin has been internally drained basin since initial subsidence of the basin in the Cenozoic. This inference is supported by recent source‐to‐sink studies that reveal that exhumation of the Altyn Tagh Shan, Eastern Kunlun Shan and the Qilian Shan source regions has provided clastic material to the Qaidam basin since the deposition of Lulehe Formation (Bush et al, ; F. Cheng, Fu, et al, ; F. Cheng, Guo, et al, ; F. Cheng, Jolivet, et al, ; F. Cheng, Jolivet, et al, ; L. Li et al, ; L. Li et al, ; W. Wang, Zheng, et al, ; W. Zhu, Wu, Wang, Fang, et al, ; W. Zhu, Wu, Wang, Zhou, et al, ).…”
Section: Methodsmentioning
confidence: 80%
“…where M erosion is the total mass of the materials eroded from the Altyn Tagh Shan, Qilian Shan, and Eastern Kunlun Shan, M basin fill is the total mass of the deposits preserved in the Qaidam basin, and M escape is the mass of eroded sediment flux from the Qaidam basin. Based on seismic profile interpretation and field investigation (F. Cheng, Guo, et al, ; F. Cheng, Jolivet, et al, ; L. Wang et al, ), a Miocene regional angular unconformity between the upper and lower Xiaganchaigou Formation has been identified. Although this unconformity likely indicates the erosion of the pre‐Miocene strata within the basin during the Miocene, those eroded materials would be transported by local drainage systems and again deposited within the basin given the prevalence of closed‐basin conditions since at least ~30 Ma (Bush et al, ; F. Cheng, Fu, et al, ; W. Wang, Zheng, et al, ) and the late Pliocene to early Pleistocene onset of wind erosion in the basin (Heermance et al, ; Kapp et al, ; Pullen et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have demonstrated that the Cenozoic contractional structures in the Qilian Shan region accommodated sizable left‐lateral displacement along the Altyn Tagh Fault [e.g., Métivier et al ., ; Meyer et al ., ; Tapponnier et al ., ; Yin et al ., , ; Cheng et al ., ]. These studies suggested that the migration of the loci of thrust faulting and crustal shortening was guided by the propagation of the Altyn Tagh Fault and led to the formation of distant, parallel, and narrow ranges.…”
Section: Tectonic Implicationmentioning
confidence: 99%
“…The Altyn Tagh Fault zone extends ~2000 km along strike and is a major left‐lateral, strike‐slip fault zone that is thought to accommodate 375–400 km of slip that was imposed by the northeastward extrusion of the Tibetan Plateau during the Cenozoic [ Cowgill et al ., ; Peltzer and Tapponnier , ; Yang et al ., ; Yin et al ., ; Yue et al ., , ]. Slip on the fault has been absorbed by deformation within the western margin of the Qaidam Basin [ Fang et al ., ; Yin et al ., ] and by folds and the south dipping thrust fault system in the Qilian Shan region [ Meyer et al ., ; Wang et al ., ; Cheng et al ., ]. The North Qilian Shan Fault is an active thrust fault in the study region.…”
Section: Geological Settingmentioning
confidence: 99%